Studies on the synthesis of the lasubine alkaloids - Simon, Oliver (2019)
Formal syntheses of lasubine II and subcosine II have been completed by the synthesis of epi-lasubine II. The synthesis involves diastereoselective allylation of a methoxy isoxazolidine and a tandem hydrogenation process leading stereoselectively to a trisubstituted piperidine.